Environmental Governance Urban: Public Participation and Sustainable Development - Darhamsyah, Darhamsyah (International Journal of Environment, Engineering & Education, 2019)
Environmental protection and management are carried out based on the principle of state responsibility, sustainability and sustainability, harmony and balance, integration, benefits, prudence, justice, ecoregion, biodiversity, participatory, local wisdom, good governance, and regional autonomy. The purpose of the research is to find out how much influence obtained between the variables of participation in sustainable development and indicators on these variables in environmental management in urban areas. The study was conducted in Makassar City in 2017-2018 with questionnaires and interviews as instruments to obtain primary data. The number of samples used was 200 respondents. With variables consisting of participation and sustainable development, then the indicator includes of (1) Thought Contribution; (2) Contributions of Funds; (3) Energy Contributions and (4) Contributions of Facilities for participation variables and (1) Culture - Ecology Interface; (2) Culture - Economy Interface; and (3) Economy - Ecology Interface for sustainable development. The analysis used is Confirmatory Factor Analysis (CFA) and to manage primary data with CFA, the help of IBM AMOS 23 Software used. The results of the study show that community participation in the development of business entities and waste banks is to encourage public involvement to the lowest level. To support environmental sustainability at the local level this, form of participation. From such things that make a significant influence between community participation in the development of environmental sustainability.